The Multiple Extended Tidal Tails of NGC 288 - Carl J. Grillmair (The Astrophysical Journal)
Using photometry and proper motions from Pan-STARRS, DECaLS, and Gaia Data Release 3, we detect a ∼35°–70° long trailing stellar debris stream associated with the globular cluster NGC 288. The trajectory of the trailing tail is not well matched by a model stream evolved in a static Galactic potential, but is reasonably well matched by a stream modeled in a potential that incorporates a massive, infalling Large Magellanic Cloud. We also detect a broad, at least ∼40° long leading tail that appears to be composed of at least two narrower, spatially offset, and kinematically distinct streams. Stream modeling predicts a similar broad composite of streams and suggests that these narrower components could each be made up of one or more generations of tidal tails, each formed during different orbits over the past few gigayears. On the other hand, NGC 288 is believed to have been brought into the Galactic halo during the Gaia–Enceladus–Sausage accretion event, and the tangential velocity dispersions of our stream candidates are indeed mostly consistent with having been stripped in a parent galaxy that had a large, cored dark matter halo. Tables of the most highly ranked stream star candidates are provided for ongoing and future spectroscopic surveys.